The approach of Abdullah bin Shubar in explaining the reasons for the descent (Journal of the College of Basic Education, 2022)
The commentators have taken care in their interpretations of the reasons for the descent and singled out many classifications for it. Because the reasons for revelation play an influential role in explaining the meaning of the Qur’anic verse and its dimensions and purposes. In explaining the reasons for the revelation, he followed several approaches, such as mentioning the reasons for the revelation in the introduction to the interpretation of the verse, or he explains the verse because of the revelation, or he mentions the sayings of some of the commentators on the reason for the verse, then gives preference to the more correct saying, or he explains the reason for the revelation specific to the incident, then he determines that the ruling is general and that the reason is specific. And other methods mentioned in the research.